Quality of Service of the Bandar Deli Passenger Terminal, Belawan Port at PT PELINDO I - Ahmad Fauzan; Asima Yanty Sylvania Siahaan (Publik : (Jurnal Ilmu Administrasi), 2026)
The increasing demand for quality public services in the transportation sector requires port operators to improve service delivery to ensure passenger satisfaction and competitiveness. This study examines the service quality of the Bandar Deli Belawan Passenger Terminal managed by PT Pelindo I, which plays a strategic role as a major passenger gateway in North Sumatra. Using a qualitative approach, data were collected through observation, interviews with key, main, and additional informants, as well as documentation. The analysis employed the SERVQUAL model, covering five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that the tangible dimension remains inadequate due to limited facilities and infrastructure, while reliability is constrained by delays in ship departure schedules. Responsiveness is considered good, as officers are relatively quick in handling passenger needs and complaints. Assurance is fairly well implemented, although security monitoring facilities such as CCTV require improvement. Empathy is rated positively, as staff generally demonstrate friendliness and professionalism. The study concludes that service quality at the Bandar Deli Belawan Passenger Terminal is still uneven across dimensions, requiring improvements in waiting room facilities, parking areas, schedule management, and security systems to enhance overall service delivery. This research contributes to the discourse on public service quality in the port sector and offers practical insights for improving passenger terminal services in Indonesia.